ANALYSIS OF WEED VEGETATION ON OIL PALM PRODUCING PLANTS (Elaeis guineensis Jacq.) AT PT. PERKEBUNAN NUSANTARA IV UNIT KEBUN BAH JAMBI: ANALISIS VEGETASI GULMA PADA TANAMAN MENGHASILKAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI PT. PERKEBUNAN NUSANTARA IV UNIT KEBUN BAH JAMBI - Reza Salima; Husein Abdullah, Umar; Nazahah (PT. ROCE WISDOM ACEH, 2025)
This study aims to determine the type of dominant weeds and the level of weed density that can interfere with the growth of oil palm plants (Elaeis guineensis Jacq.) at PT. Perkebunan Nusantara IV Bah Jambi Garden Unit. This study uses the quadrat method used to identify weeds. A plot of research area was made of as many as 2 blocks of oil palm plantation land in the same planting year. Sampling was carried out by direct sampling using a plot size of 1 mx 1 m with a total of 5 sheets thrown on each block. The results of this study indicate that the dominant weeds and the level of weed density can interfere with the growth of oil palm plants at PT. Perkebunan Nusantara IV Unit Kebun Bah Jambi are Axonopus Compressus .